Innovative Mechanisms for Managing the Digital and Regional Economy - Abdullayeva, I. M.; Mirodilova, D. M. (European Journal of Life Safety and Stability (2660-9630), 2022)
The digital strategy focuses on working with citizens through data operations. E-government is proposed to be understood as a form of implementation of public administration based on the synergistic interaction of ICT and information resources (data) in order to provide public services. The negative factors hindering the development of e-government in our country are also highlighted, and possible ways to overcome them are outlined.